RADIOTHERAPY RESPONSE IN ADVANCED STAGE OF CERVICAL CANCER TYPES OF HISTOPATHOLOGY SQUAMOS CELL CARCINOMA AND ADENOCARCINOMA - Sindunata, Natasha Bharat; Pratiwi, Eka Indah; lubis, arlavinda asmara (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2024)
Background: Cervical cancer is a malignancy that occurs on the cervix, and it is the most common cancer in the world. According by GLOBOCAN in 2020, cervical cancer ranks seventh globally. The main management of advanced cervical cancer is using radiotherapy. The problem that occurs is the need for radiation for advanced cervical cancer patiens while there is still a lack of availability of radiotherapy equipment, causing under treatment management.Objective: To prove that the response to radiotherapy in patients with advanced cervical cancer types of histopathology squamous cell carcinoma is better than adenocarcinoma in Ulin General Hospital, BanjarmasinMethods: The study used an analytic observational design with a cross sectional approach. The sample was taken over the time span during the study from January 2021 to December 2022 and was taken by total sampling.Results: The total sample was 128 cervical cancer patients with 91 squamous cell carcinoma samples and 37 adenocarcinoma samples. After conducting a chi-square analysis between several variables and response to therapy, a significant relationship was found between histopathology and response to therapy, which concluded that cervical cancer with histopathology of squamous cell carcinoma is more radiosensitive than adenocarcinoma. This is due to the relationship between VEGF and radiation.Conclusion: The response of radiotherapy is more sensitive in type of histopathology squamous cell carcinoma than in cervical cancer with type of histopathology adenocarcinoma.